Kinerja Keuangan Daerah Kabupaten Halmahera Selatan - Aswir Hadi; Ahmad Yani Abdurrahman (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research aims to determine the financial performance of South Halmaherah Regency in 2010-2017 This research is a case study research with data collection using library techniques, and the data used are secondary data in the form of a report on the realization of the South Halmahera Regency revenue and expenditure budget in 2010-1017 . Furthermore, this data is calculated using financial ratios namely the ratio of the degree of fiscal decentralization, the ratio of financial independence, the ratio of effectiveness of PAD, and the ratio of regional financial efficiency.The results showed that in general the financial performance of the government of South Halmahera Regency was not optimal. Based on the results of the study, it can be illustrated that the financial performance of local governments in South Halmahera Regency is still not stable or not so good. Where the results of calculations in each year are still experiencing numbers that fluctuate so that some financial ratios still show positive trends and negative trends. This is caused by the regional government of South Halmahera Regency which is not yet mature in the management of available regional resources. This can be explained from research that uses several financial ratios including the ratio of the degree of fiscal decentralization, the ratio of regional financial independence, the ratio of effectiveness, and the efficiency ratio of regional finances.